EFEKTIVITAS PROGRAM ERADIKASI KASUS HIV/AIDS DI KALANGAN BERESIKO - Rianita Siagian; Felix Kasim (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
The number of HIV cases in Indonesia is growing rapidly both in terms of distribution area and distribution pattern. This research aims to conduct an in-depth analysis of Program Effectiveness in the risk areas of HIV / AIDS Cases in Risk of Work Areas in the Health Center Tehnical Implementation Unit Padang Bulan in 2019. Data are obtained through interviews with the Head of Community Health Center, VCT Responsible Agency, Health Promotion Responsible in Health and some informants at risk area, this is supported by the results of participant observations on VCT which always provide support to those at risk for examining HIV / AIDS as well as explaining the symptoms caused by HIV / AIDS. From the results of the analysis with the Triangulation method, it can be concluded: Input (SDM that has multiple function assignments listed in the Organizational Structure and limited funds when conducting risk areas of HIV / AIDS cases in accordance with the Planning Of Action), Process (constraints, efforts, expectations and health center program benefits are not yet in line with the behavior of the risk groups in the community, this is seen from the circles), Output (people with HIV / AIDS or ODHA who are free to follow up and there is still an assumption that people at risk are HIV and AIDS are the same and not yet behavior change in risk). The conclusion in this research is that the program in eradicating HIV / AIDS cases in the Health Center Tehnical Implementation Unit Padang Bulan is still not effective. Suggestions in this research are that the health center are expected to revitalize work programs in eradicating HIV / AIDS cases starting from planning, implementation, monitoring and evaluation so that the program runs more effectively